Konsep Mencintai Diri Sendiri dalam Lirik Lagu Maria dan I’m a Bit - Madania, Shafira; Luthfiarrahman, Annisa; Latifah, Eva (East Asian Review, 2025)
The concept of self-love is discussed in various Korean media, including K-pop. One K-pop singer who tends to raise awareness about this concept in her songs is Hwasa from the girl group Mamamoo. Hwasa has participated in writing some of her songs that shed light on the concept of self-love, such as “Maria” (2020) and “I’m a Bit” (2021). The goal of this research is to explain the concept of self-love in both songs. This research used the theory of self-love by Henschke & Sedlmeier (2021) to determine the categories of self-love. The method being used is content analysis through qualitative descriptive approach. The research is done by gathering data from the lyrics of both songs and analyzing the elements of self-love shown in it. The result of the research showed the concept of all three categories of self-love in both song lyrics, which include self-contact, self-acceptance, and self-care. Both “Maria” and “I’m a Bit” used wordplays and expressions to deliver the song message implicitly. Despite having the same message, both songs differ in language styles. “Maria” has two different parts which are calming and provocative, meanwhile “I’m a Bit” is more frank, explicit, and playful.